The Effect of 50 000 IU Vitamin A with BCG Vaccine at Birth on Growth in the First Year of Life - Fisker, Ane Bærent (Hindawi Publishing Corporation, 2011)
Vitamin A supplements may interact with diphtheria-tetanus-pertussis (DTP) vaccine causing increased female mortality. In a randomised trial of neonatal vitamin A supplementation (VAS), we examined growth during the first year of life in 808 children, pursuing the hypothesis that a negative interaction between VAS and DTP in girls would be reflected in growth. Length and weight were measured at 6 weekly visits and WHO-growth-reference z-scores derived. Neonatal VAS had no effect on anthropometric measures at 12 months, but may interact sex differentially with routine vaccines. While BCG was the most recent vaccine, neonatal VAS benefitted growth (difference in weight-for-length z-score (dWFL: 0.31(95% CI: 0.03–0.59)). While DTP was the most recent vaccine, VAS tended to affect growth adversely in girls (dWFL = −0.21 (−0.48–0.06)). After measles vaccine (MV) there was no overall effect of neonatal VAS. The VAS effect differed significantly between the BCG and DTP windows (P = 0.03), and the difference was borderline significant between the DTP and MV windows for girls (P = 0.09).